Meat protein quality of Dormitator latifrons (Pisces: Eleotridae): arguments for use by rural communities - Rafael Basto-Rosales, Mao Ernesto; Carrillo-Farnés, Olimpia; Montoya-Martínez, Cynthia Eugenia; Badillo-Zapata, Daniel; Rodríguez-Montes de Oca, Gustavo Gustavo; Álvarez-González, Carlos Alfonso; Nolasco-Soria, Héctor; Villasante, Fernando Vega (Ecosistemas y Recursos Agropecuarios, 2019)
The objective of this study was to evaluate the quality of meat protein of Dormitator latifrons for humans based on its Protein Digestibility Corrected Amino Acid Score (PDCAAS). Wild and cultured specimens were evaluated for amino acid content using HPLC equipment. The calculation of PDCAAS was performed as follows: milligrams of essential amino acid in 1 g of test protein per milligram of the same amino acid in 1 g of reference protein per true digestibility. To evaluate the protein of D. latifrons in relation to that of other fish, PDCAAS was calculated from the proteins of eight fish usually used in human nutrition. D. latifrons has a good essential amino acid profile, providing the same nutritional quality as those of other fish. Although the meat of wild D. latifrons contributes only 73% of human lysine requirements, it can be complemented with other lysine sources.
Keywords: Essential amino acids; human nutrition; limiting amino acid; native fish; muscle protein; low-income communities